PELAKSANAAN FUNGSI LAYANAN BK KELAS X DI SMA NEGERI 1 SEBERUANG KABUPATEN KAPUAS HULU - Laurensius Allo Khastro; Yuline Yuline; Sri Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to find out the implementation of counseling service functions in first grade ed SMA 1 Seberuang and to know the students' responses to the implementation of Counseling service functions. The function of Counseling services in this study was the function of understanding, prevention functions, alleviation functions and maintenance and development functions. The form of this study was a survey study (servey studies) with a population of 126 students and a sample of 40 students. The data collection tool used was a questionnaire. By the results of this study, researcher found out that the implementation of the Counseling service  results in a percentage of 83.38% and students' responses to the implementation of the Counseling service function are percentage results of 83.96%. Thus, the Counseling teacher has implemented the function of understanding, prevention functions, alleviation functions and maintenance and development functions. Students responses to the implementation of Counseling functions can be categorized as "Good". Keywords: Functions,Guidance Counseling,  Implementation, Service